Growing (Un)equal : Fiscal Policy and Income Inequality in China and BRIC+ - Cevik, Serhan; Correa-Caro, Carolina (Washington, D.C. : International Monetary Fund, 2015)
This paper investigates the empirical characteristics of income inequality in China and a panel of BRIC+ countries over the period 1980-2013, with a focus on the redistributive contribution of fiscal policy. Using instrumental variable techniques to deal with potential endogeneity, we find evidence supporting the hypothesis of the existence of a Kuznets curve-an inverted Ushaped relationship between income inequality and economic development-in China and the panel of BRIC+ countries. In the case of China, the empirical results indicate that government spending and taxation have opposing effects on income inequality. While government spending appears to have a worsening impact, taxation improves income distribution. Even though the redistributive effect of fiscal policy in China appears to be stronger than what we identify in the BRIC+ panel, it is not large enough to compensate for the adverse impact of other influential factors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet